Boavista, uma avenida na história da cidade. O contributo da análise de variâncias e permanências para as estratégias de intervenção - Maria Manuel dos Reis Cunha (2017)
This dissertation's theme of study is the analysis of variations and permanencies of a part of Avenida da Boavista in the city of Oporto. This consolidated section of the city displays a multiplicity of structures built over the years, that together show a huge formal and architectural variation. In one hand, since the segment has bourgeois matrices and at the same time contemporary house blocks, there are analysed the origin factors of the profound typological transformations, that represent a break with the traditional consolidated models and which led to demolitions, ruptures and a loss of identity of the segment in study. On the other hand, we focused our attention on the bourgeois matrices of the liberal period, performing a thorough study of its variations and obtaining an in-depth knowledge which supports the preservation and rehabilitation of this typology instead of its demolition. Due to the complexity of the theme, there was the need to explore two different points of view: a firm focus on the architectural issue of the building as an object and, simultaneously, to increase the knowledge about the urbanistic logic, taking the object as an integral and determinant part of a more vast network- the city. This study performs an in-depth analysis of one of the segments of Oporto city, discussing and presenting intervention strategies that address the two points of the analysis: regeneration of the urban network and rehabilitation of the bourgeois housing of the liberal period, being elaborated a prototype of rehabilitation for this last point.